PENDEKATAN ISTIKAMAH MODEL SUPERVISI PENINGKATAN KINERJA GURU PAI DI SMP NEGERI KABUPATEN NAGAN RAYA - Herman Herman (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2020)
This article aims to describe how istikamah approach can be a moral force for the supervisors of PAI (Islamic Education) in running their main tasks and functions to supervise the teachers of PAI. The attitudes and behavior of Istikamah of PAI supervisors will form kindness, virtuousness, and good work accomplishment in the attempts to improve PAI teacher's performance. The phenomena in the field show that the supervisors of PAI have not internalized the attitude and behavior of istikamah when acting as the supervisors, stimulators, and motivators in supervising, guiding, and improving the performance of PAI teachers. The study was carried out in a qualitative approach utilizing a descriptive design. The subjects of the study were 2 PAI supervisors and 20 PAI teachers in state junior high schools in Nagan Raya district. Data collection was performed through observation, interview, and documentation. Referring to Miles and Huberman, data analysis was carried out by following some procedures comprising data reduction, data computation, and drawing a conclusion. In addition, the validity of the data was examined through the triangulation of the sources, methods, and theories. The result of the study pointed that PAI supervisors have implemented istikamah approach in the model of consistency toward aqeedah tauhid, consistency toward Islamic law, consistency toward truth and justice, consistency toward subjecting the worldly temptation, and the model of working with full commitment in improving the performance of PAI teachers.